Molecular (Raman, NIR, and FTIR) spectroscopy and multivariate analysis in consumable products analysis1. Issue 8 (13th September 2020) - Fakayode, Sayo O.; Baker, Gary A.; Bwambok, David K.; Bhawawet, Nakara; Elzey, Brianda; Siraj, Noureen; Macchi, Samantha; Pollard, David A.; Perez, Rocio L.; Duncan, A'ja V.; Warner, Isiah M.
Abstract: Ensuring the integrity of quality control and assurance of consumable products across consumer goods distribution and supply chains is pertinent to ensure consumer products of high quality to guarantee public health. Several analytical strategies, and technological innovations have been developed over the years for the quality control and assurance of consumable products. However, the simplicity and the noninvasive and nondestructive properties of Raman, near-infrared (NIR), and Fourier-transform infrared (FTIR) spectrometers, coupled with the low-cost and portability make these instrumental techniques excellent tools of choice for quality control and assurance of consumable products. This review article examines recent technological innovations and advances in Raman, NIR and FTIR spectroscopic instrument development and multivariate analyses used in consumer product analysis. New innovations in Raman, NIR, and FTIR spectroscopies as applied to analytical method development for purity analysis, quality control and assurance of consumable food products between January 2015 and December 2018 are discussed. Applications of data processing strategies and multivariate analyses of spectral data for instrumental and sample calibration, chemical analysis, and pattern recognition of consumable products are presented. The review also provides insight into the future trajectory of innovative technological developments in molecular spectroscopy, and multivariate analyses pertaining to general applications for consumer product analysis.